PENGARUH PROGRESIVE MUSCLE RELAXATION TECHNIQUE TERHADAP KECEMASAN PASIEN PRE OPERASI BEDAH MAYOR DI RUMAH SAKIT MUHAMMADIYAH PALEMBANG - sukron sukron (Masker Medika, 2023)
Introduction: Major surgery is a stressor that is quite severe for patients and can evoke stress reactions psychologically in the form of anxiety. Preoperative anxiety must be handled immediately by nurses to minimize complications that can occur after surgery, because they can cause physiological changes. Objective: To determine the effect of progressive muscle relaxation technique on the anxiety of patients with pre-major surgery at Muhammadiyah Palembang Hospital. Methods: This study used a pre-experimental approach with a pretest-posttest one group design without control approach. The population includes all patients pre-major surgery in January-February 2022 with a sample of 19 respondents and was taken by consecutive sampling. Hypothesis testing was carried out using the Paired Samples T-test in the form of a dependent t-test with a significance level of α 0.05. Results: The average anxiety before the progressive muscle relaxation technique intervention was 21.95, and after the intervention was 20.53. Then based on data analysis it is known that there are differences in anxiety levels before and after being given progressive muscle relaxation therapy with a p-value of 0.015. Conclusion: There are differences in the level of anxiety before and after the progressive muscle relaxation technique therapy at the Muhammadiyah Palembang Hospital